Discovery and biochemical characterization of a mannose phosphorylase catalyzing the synthesis of novel β-1,3-mannosides - Awad, Faisal Nureldin; Laborda, Pedro; Wang, Meng; Lu, Ai Min; Li, Qian; Cai, Zhi Peng; Liu, Li; Voglmeir, Josef (Biochimica et biophysica acta. General subjects, 2017)
Mannoside phosphorylases are frequently found in bacteria and play an important role in carbohydrate processing. These enzymes catalyze the reversible conversion of β-1,2- or β-1,4-mannosides to mannose and mannose-1-phosphate in the presence of inorganic phosphate. The biochemical parameters of this recombinantly expressed novel mannose phosphorylase were obtained. Furthermore purified reaction products were subjected to ESI- and MALDI-TOF mass spectrometry and detailed NMR analysis to verify this novel type of β-1,3-mannose linkage. We describe the first example of a phosphorylase specifically targeting β-1,3-mannoside linkages. In addition to mannose, this phosphorylase originating from the bacterium Zobellia galactanivorans could add β-1,3-linked mannose to various other monosaccharides and anomerically modified 5-bromo-4-chloro-3-indolyl-glycosides (X-sugars). An unique bacterial phosphorylase specifically targeting β-1,3-mannoside linkages was discovered. Functional extension of glycoside hydrolase family 130. [Display omitted] •Mannoside phosphorylases are frequently found in bacteria and play an important role in carbohydrate processing.•A bacterial phosphorylase catalyzes the reversible phosphorolysis of novel β-1,3-oligomannose structures.•Discovery of an enzyme specifically targets β-1,3-mannoside linkages.•Functional extension of glycoside hydrolase family 130